Efektivitas Peran Gembala Jemaat dalam Pertumbuhan Gereja - Yulia Santoso (Sekolah Tinggi Alkitab Jember, 2020)
This article is a research result of the role of the pastor's effectiveness in church growth. As for the object examined in this thesis in accordance with the context of the pastor,